Optimum potassium fertilizer rate for growth, biomass yield, and fuel properties of Leucaena (Leucaena leucocephala) cv. Tarramba in sandy soil - Nitthaisong, P.; Thupwong, K.; Tonmukayakul, N.; Utharapan, J.; Chaisan, T.; Rungmekarat, S.; Tudsri, S.; Chotchutima, S. (My University, 2025)
The results showed that the 187.5, 375 and 750 kg ha-1 application rates increased plant height and stem diameter, while the control (0 kg ha-1) showed a potassium deficit, resulting in stem dieback. High leaf, branch, and stem yield were found at application rates greater than 93.75 kg ha−1, while plant height, stem diameter and biomass yield were slightly further increased in the 187.5, 375 and 750 kg ha-1 treatments. Regarding fuel properties, the potassium application rate did not affect the heating value and ash content but decreased the N and S contents. The potassium content tended to increase with increased potassium application rate. However, the leucaena wood under all the treatments had suitable fuel properties for use as a fuel crop.
Keywords: Biomass yield; Fuel properties; Leucaena; Potassium fertilizer; Sandy soil